Bushmeat consumption in large urban centres in West Africa - Luiselli, L.; Hema, E.M.; Segniagbeto, G.H.; Ouattara, V.; Eniang, E.A.; Parfait, G.; Akani, G.C.; Sirima, D.; Fakae, B.B.; Dendi, D.; Fa, J.E. (Cambridge University Press, 2020)
There is an unprecedented demand for bushmeat in large cities in sub-Saharan Africa, and this is a major threat to many species. We conducted 2,040 interviews in six cities in four West African countries, in forest and savannah settings. We analysed age- and sex-related differences in the frequency of bushmeat consumption. Overall, we found similar patterns in all cities: 62.2% of men and 72.1% of women said they would never eat bushmeat, whereas 12.8% of men and 8.8% of women said they liked bushmeat and ate it regularly. Younger generations of both sexes tended not to eat bushmeat, regardless of their city of origin. This study of the effects of age, gender and geographical location on bushmeat consumption in African cities provides insights regarding which population groups to target in campaigns to change behaviours.